Kerkvereniging en Kerkreg: Geskiedenis, beginsel en praktyk - Hofmeyr, J. W. (Verbum et ecclesia, 1996)
Church unity and church polity: History, principle and practice In this article the need for a clearer focus on the history, principles and practice of church polity in the process of church re-unijication is addressed. This is specijically focused on the process currently under way in the Dutch Reformed Church family. After an extensive discussion of issues pertaining to the history, principl~s and practice of church polity within this church family, it is concluded that the process of re-unijication need to be implemented with the necessary urgency, but also with patience.